IMPLEMENTASI PERATURAN BUPATI SRAGEN NOMOR 10 TAHUN 2018 TENTANG PETUNJUK PELAKSANAAN PERATURAN DAERAH NOMOR 8 TAHUN 2017 TENTANG PERANGKAT DESA DI DESA JEKAWAL, KECAMATAN TANGEN, KABUPATEN SRAGEN, JAWA TENGAH - Tri Giyanto (JI@P, 2020)
One of the villages in the Sragen Regency region that conducts village apparatusselection (perdes) is Jekawal Village, which is included in the Tangen District area.The implementation of village apparatus selection (perdes) in Jekawal Village wentsmoothly, the selection stage was carried out twice, namely mutation selectionbetween village apparatuses with below standard selection results, so that selectionwas continued from the general public. The selection of village officials (perdes) inJekawal Village went smoothly according to Sragen Regent Regulation Number 10 of2018 concerning Guidelines for Implementing Regional Regulation Number 8 of2017.Implementation of Sragen Regent Regulation Number 10 of 2018 concerningGuidelines for Implementation of Regional Regulation Number 8 of 2017 concerningJekawal Village Apparatus, Tangen District, Sragen Regency has been going well.The implementation of the policy uses the model of Merilee S. Grindle, namely: 1.Contents of the Policy: 1) Objective: a reference for filling out the Village Apparatus.2) Change: The process is running optimally. 3) Interests: The interests of the wholecommunity. 4) Benefits: Process is more optimal. 5) Implementer .: Village ApparatusSelection Team. 2. Policy context 1) Power: Strength: (1) Human resources. (2)Facilities and infrastructure. (3) Communication. (4) Technology. Weaknesses:limited operating budget. 2) Strategy: Implement all policies according toregulations. 3. Policy Results: 1) Accuracy of target groups: All members of thevillage community. 2) Conformity of implementation: In accordance with applicablerules. Factors for the successful implementation of the Edward III model are: 4.Resources: 1) Human Resources (HR): sufficient. 2) Funds: Village income andexpenditure budget. 3) Technology: Enough. 4) Facilities / infrastructure: Sufficient.5. Communication: Dissemination to the RT level. 6. Disposition (implementingattitude): Good attitude, enthusiasm and professionalism. 7. SOP bureaucraticstructure: SOP of Jekawal Village Apparatus.